Analysis of Resilience Levels Among Adolescents Experiencing Symptoms of Childhood Inner Wounds - Lailshalma Yuniar; Gian Sugiana Sugara; Anandha Putri Rahimsyah (Edupotensia Foundation, 2026)
This study aims to describe the level of resilience in students who have experienced trauma. inner child at SMPN 2 Tasikmalaya. This study used a quantitative method with a descriptive design and involved 242 eighth-grade students as participants. Data were obtained through the distribution of resilience and wounded identity instruments. inner child , which was then analyzed using descriptive statistics. The results showed that the level of student resilience varied into three categories: high, medium, and low. The majority of students were in the medium resilience category with a percentage of 59.09%, while the high resilience category was 21.49% and the low category was 19.42%. Analysis based on dimensions showed that the personal and relational resilience dimensions were dominated by the medium category, indicating that students had quite good adaptation skills but still needed strengthening. This finding illustrates that although students have had wounded experience inner Most children were able to maintain adequate psychological resilience. The results of this study are expected to form the basis for developing counseling intervention programs to optimally enhance resilience in school settings.